2018
DOI: 10.14474/ptrs.2018.7.3.139
|View full text |Cite
|
Sign up to set email alerts
|

Risk of falls in community-dwelling older adults aged 65 or over with type 2 diabetes mellitus: a systematic review

Sujin Hwang

Abstract: Objective: Older persons with diabetes mellitus (DM) are particularly more likely to have fallen in the previous year than those without DM. The purpose of this study was to investigate the relationship between the risk of falls and type 2 DM in older adults who are 65 years of age or above. Design: A systematic review. Methods: PubMed and other two databases were searched up to August 2, 2018. Observational and cohort studies evaluating fall risk in people who are 65 years of age or above with DM were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Em vários estudos associam a ocorrência de hipoglicemia e quedas, sendo a hipoglicemia é um fator de risco três vezes maior para quedas, especialmente para pacientes acometidos por diabetes e idosos. Outra condição de risco é a hipotensão ortostática (Hwang, 2018;Khow & Visvanathan, 2017;Shah et al, 2018).…”
Section: Resultsunclassified
“…Em vários estudos associam a ocorrência de hipoglicemia e quedas, sendo a hipoglicemia é um fator de risco três vezes maior para quedas, especialmente para pacientes acometidos por diabetes e idosos. Outra condição de risco é a hipotensão ortostática (Hwang, 2018;Khow & Visvanathan, 2017;Shah et al, 2018).…”
Section: Resultsunclassified
“…Previous review of this research project identified that the risk factors of falls were impaired cognitive function, peripheral nerve dysfunction, visual impairment, and physical dysfunction in community-dwelling persons who had 65 years of age or above with T2DM [5]. This study investigated therapeutic exercises as a fall prevention strategy to improve the risk of falls in community-dwelling older adults with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous review of this systematic review, we identified the relationship between the risk of falls and type 2 diabetes mellitus (T2DM) in older adults who are 65 years of age or above. The results of the review reported that they have increased risk of falling caused by cognitive dysfunction, peripheral nerve dysfunction, visual impairment, and physical function level [5]. Chapman et al [6] investigated the first systematic review and meta-analyses of exercise in-terventions for the improvement of fall-related outcomes among older adults with DM, with the aim of quantifying the effectiveness of interventions, relative to control conditions and to assist in tailoring future interventions to meet the needs of the growing population of older adults with DM.…”
Section: Introductionmentioning
confidence: 99%
“…Physical disability acquired through falls is difficult to recover, and it is considered as a serious health issue because of the high risk for complications when compared with the younger population [5,6]. In addition, normal activities are limited by not only physical impairments, but also by fear of falling, and furthermore, there is a decrease in physical function, resulting in a high risk for falls [7].…”
Section: Original Articlementioning
confidence: 99%